Constructing Model and Measuring Level of Workplace Spirituality among Information Technology Employees in India - Alnishal P N; P. Balasubramanian (Communications of International Proceedings, 2022)
This paper examines workplace spirituality model and measuring. It also shares the level of workplace spirituality (WPS) among information technology sector in India. The data has been collected from 630 employees from Kerala and it has been analysed using structural equation model by SPSS 23 and AMOS 24 using. Compassion, transcendence, self-practices, meaningful work and mindfulness has been taken as dimensions to measure workplace spirituality. The data has been collected using structured questionnaires with 5-point Likert scale. The study concludes that existence of workplace spirituality is in a medium level among IT employees. It illustrates that there is still high scope of improvement in this area.
Keywords: Work place spirituality (WPS); Information technology sector (IT); Measuring workplace spirituality; constructing scale for Work place spirituality.